Artificial hibernation/life-protective state induced by thiazoline-related innate fear odors - Tomohiko Matsuo (Nature Portfolio, 2021)
Matsuo, Isosaka, et al report that innate fear, but not learned fear, in mice results in systemic hypothermia/hypometabolism and suppressed aerobic metabolism, which enables survival in hypoxic environments. They demonstrate that this process is orchestrated via the brain stem Sp5/NST to midbrain PBN pathway. This study provides insight into the relationship between innate fear and its intrinsic life protective abilities